(untitled) (Research, Society and Development, 2020)
The objective of this work was to test the toxic effect of different concentrations of hydroalcoholic extract of the Baccharis dracunculifolia plant, using Zebrafish (Danio rerio) larvae of 8 days’ post fertilization. In the first assay, 50.0, 25.0, 12.5, 6.25, 3.125, 1.563 and 0.781 mg mL-1 of extract were diluted in H2O and observations at 0, 1 and 2 hours of the larvae exposed to the extract were made. In the second assay, the dilutions were 2.0, 1.0, 0.40 and 0.20 mg mL-1 of extract in H2O and exposure of the larvae on the extract at 0, 4, 8 and 12 hours. From the development of the two tests it can be seen that when the larvae were exposed to extracts of B. dracunculifolia with dilutions higher than 2.0 mg mL-1, 100% mortality was obtained as soon as the larvae was exposed. The exposure of larvae of Zebrafish (Danio rerio) to eight days after fertilization at the different dilution levels of the hydroalcoholic extract of B. dracunculifolia showed lethal effects. However, when dilutions were tested from 0.40 mg mL-1, a low percentage of mortality was obtained.